Mental health trajectories of Brazilian health workers during two waves of the COVID-19 pandemic (2020–2021) - de Lima Osório, Flávia; Zuardi, Antônio Waldo; Silveira, Isabella Lara Machado; de Souza Crippa, José Alexandre; Hallak, Jaime Eduardo Cecílio; Pereira-Lima, Karina; Loureiro, Sonia Regina (Frontiers in Psychiatry, 2023)
This study aimed to: a) monitor the progression of symptoms of mental health burden among frontline workers caring for COVID-19 patients in Brazil during the two waves of the pandemic, considering the number of new cases and deaths, and; b) to verify the different mental health outcomes and potential associations with current burnout symptoms. A non-probabilistic sample of health professionals was assessed as the pandemic progressed in Brazil (May/2020 August/2021). Standardized instruments focusing on anxiety, depression, insomnia, post-traumatic stress, and burnout symptoms were applied online. The results indicate a decrease in anxiety levels, what was related to when the number of new cases declined (end 1th-wave); symptoms returned to higher levels later. Emotional exhaustion increased when there was a higher incidence of cases, returning to the baseline levels at the end of the second wave. Depersonalization symptoms increased in this phase, characterized by a further decrease in new cases, while professional accomplishment decreased during the follow-up. The highest number of new cases was associated with a higher frequency of anxiety (OR=1.467;95%CI=1.109-1.941;p=0.007) and professional accomplishment (OR=1.490;95%CI=1.098-2.023;p=0.011). The subjects with trajectory of resilience against anxiety presented the lowest level of emotional exhaustion and depersonalization (p<0.05). The conclusion is that the pressure experienced by healthcare professionals throughout the pandemic caused different impacts on their mental health, emphasizing the dynamic nature of this condition and the need for constant monitoring and care. This finding directly affects mental health prevention and intervention measures, which remain a priority and require continuous reinforcement, especially among vulnerable groups.